Mitochondrial biogenesis during fungal spore germination: effects of the antilipogenic antibiotic cerulenin upon Botryodiplodia spores. - Brambl, R (1978)
Germination of spores of the fungus Botryodiplodia theobromae was inhibited by the antilipogenic antibiotic cerulenin. The spores remained viable in the presence of the antibiotic, however, and after prolonged incubation they were able to overcome the inhibition. Cerulenin inhibition of germination was reversed by Tween 40 and Tween 60 (derivatives of palmitate and stearate, respectively), but not by representatives of a range of free fatty acids or their soaps. Cerulenin abolished incorporation of [14C]acetate into sterols and triglycerides and reduced its incorporation into fatty acids by 69%. Cyanide-sensitive oxygen consumption by spores incubated in the presence of cerulenin was greatly reduced throughout germination, and the activity of cytochrome c oxidase was no more than 13% of the activity in untreated spores, even after prolonged incubation. However, low-temperature difference spectra of mitochondrial extracts showed that the cerulenin-treated spores accumulated a threefold excess of cytochrome a, whereas the cellular concentrations of cytochroms c and b were identical to those of untreated spores. Cerulenin treatment sharply reduced the rates of whole spore protein and RNA synthesis. Cerulenin had no effects upon mitochondrial morphology which could be discerned with an electron microscope.